Marchetti type of aircraft engine error detection system using hill climbing heuristic - Anton Setiawan Honggowibowo; Asih Pujiastuti; Yuliani Indrianingsih; Dhea Yogi Anugerah (Compiler, 2021)
Transportation has become a human need today, one of which is air transportation, namely airplanes. In order for the aircraft to be used properly and comfortably, it is necessary to carry out routine maintenance, especially before flying. Problems caused by aircraft engines are sometimes small problems that do not require a high level of knowledge. To overcome this, maybe someone who has very basic knowledge of aircraft engines can do it. But sometimes these problems also require a high level of expertise regarding these components so that they require technicians or experts to repair them. Through this application, users can consult the system such as consulting with experts to find out the symptoms that occur on the plane and find solutions to the problems encountered. The expert system built using the Hill Climbing Heuristic method resulted in 72.67% when tested on respondents.